Box-Behnken Modeling Served for the Development and Optimization of Nanoparticles Loaded with Perindopril and Erbumine (Asian Journal of Pharmaceutics (AJP), 2023)
Background: The study aimed to optimize and validate a nano-particulate technology for the sustained releaseof perindopril erbumine, an angiotensin-converting enzyme (ACE) inhibitor, using a box-behnken experimentalmethodology. Methods: The researcher used a Box-behnken experimental methodology to optimize theformulation and assess various characteristics such as particle size, zeta potential, surface shape, encapsulationefficiency and in vitro drug release. The nanoparticles characterization findings were recorded included the size,polydispersity index, zeta potential and encapsulation efficiency. Results: The nanoparticles had a smooth surfaceand their size was determined to be 122.38 ± 0.75 nm. The polydispersity index was 0.298, the zeta potentialwas 38.79 ± 0.05 mv and the encapsulation efficiency was 61.73 ± 0.06%. In vitro release was restricted for upto two hours, but at a pH of 7.4, the rate of drug release increased and was maintained. Conclusion: The studyconcluded that the nano-particulate technology for the potential to improve therapeutic efficacy and decreasedosage frequency for drug that need repeated doses such as perindopril erbumine.